FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PRAKTIK TAX AVOIDANCE DALAM PERUSAHAAN - Subhakti , Christian; Tjhai, Fung Njit (E-Jurnal Akuntansi TSM, 2024)
Tax avoidance is an attempt to avoid taxes legally that does not violate tax regulations. The existence of loopholes in the tax law makes tax avoidance practices often carried out by taxpayers. The purpose of this research is to obtain empirical evidence regarding the influence of transfer pricing, leverage, profitability, sales growth, institutional ownership, capital intensity, and financial distress on tax avoidance. The objects used in this research are companies in the consumer non-cyclicals and consumer cyclicals sectors listed on the Indonesia Stock Exchange for the period 2020-2022. The sample of this research used a purposive sampling method and resulted in a total of 270 data from 90 companies that met all the criteria. The method used in this research is multiple linear regression analysis. The results of this research indicate that transfer pricing influences tax avoidance. While leverage, profitability, sales growth, institutional ownership, capital intensity, and financial distress have no influence on tax avoidance